Student’s Responses to Pro-environmental Behavior-based Learning and Its Effect on Interest and Critical Thinking - Evita Anggereini; Upik Yelianti (Jurnal Pendidikan dan Pengajaran, 2023)
Good environment will affect students' learning outcomes. This study aims to analyze how students' interest in learning and critical thinking skills can be influenced by students' pro-environmental behavior, because a. This study uses a survey technique. In this study, a sample of 50 students was used which was divided into two classes. Analysis of the data used is a simple regression test. After the implementation of this research, it is known that students' responses to PEB-based learning have a significant effect on learning interest and students' critical thinking skills in learning environmental materials. This is evidenced by the t-count value which is greater than the t-table, as well as a lower significance value compared to the tolerance limit value used of 0.05. The novelty in this research is in the material being measured or tested and the number of variables used. Where in the previous study only used one of the three variables that I studied, and had not researched pro-environment. The limitations of this study are limited to knowing the effect of student responses to pro-environmental behavior-based learning (PEB) on interest in learning and student learning outcomes in environmental material learning, not yet on skills or psychomotor aspects. Therefore, it is recommended for further researchers to be able to add aspects that have not been studied in this study to make it more perfect.